A cross-sectional study of the first two years of mandatory training for doctors participating in voluntary assisted dying - Willmott, Lindy; Feeney, Rachel; Yates, Patsy; Parker, Malcolm; Waller, Katherine; White, Ben P. (Palliative & supportive care, 2024)
Voluntary assisted dying (VAD) was legalized in Victoria, Australia, in June 2019. Victoria was the first jurisdiction in the world to require doctors to undertake training before providing VAD. This study examines data from doctors who completed the mandatory training in the first 2 years of the VAD system's operation (up to 30 June 2021). It describes the doctors who are undertaking VAD training, their post-training attitudes toward VAD participation, and their experiences of the mandatory training. Through the online training, doctors completed a short demographic survey and undertook formal assessment of knowledge (90% pass mark). They also were invited to complete an optional survey evaluating the training. In total, 289 doctors passed the training, most commonly males (56%) aged 36-65 years (82%) from an urban location (72%). Most were more than 10 years post fellowship (68%) and practising as general practitioners (51%) or medical oncologists (16%). The training most commonly took 6 h (range 2 h to over 9 h). Most doctors passed the assessment at the first (65%) or second (19%) attempt. Almost all participants (97%) found the training helpful or very helpful and most reported being confident or very confident in their knowledge (93%) and application (88%) of the VAD legislation. Doctors reported the training was helpful and improved their confidence in knowing the law and applying it in clinical practice. The profile of trained doctors (particularly their location and specialty) suggests continued growth of participating doctors is needed to facilitate patient access to VAD. It is important that this safeguard does not discourage doctors' participation.